Audio quality moderates localisation accuracy : two distinct perceptual effects? - Lindborg, PerMagnus (2015)
Audio quality is known to cross-modally influence reaction speed, sense of presence, and visual quality. We designed an experiment to test the effect of audio quality on source localization. Stimuli with different MP3 compression rates, as a proxy for audio quality, were generated from drum samples. Participants (n = 18) estimated the position of a snare drum target while compression rate, masker, and target position were systematically manipulated in a full-factorial repeated-measures experiment design. Analysis of variance revealed that location accuracy was better in wide target positions than in narrow, with a medium effect size; and that the effect of target position was moderated by compression rate in different directions for wide and narrow targets. The results suggest that there might be two perceptual effects at play: one, whereby increased audio quality causes a widening of the soundstage, possibly via a SMARC-like mechanism, and two, whereby it enables higher localization accuracy. In the narrow target positions in this experiment, the two effects acted in opposite directions and largely cancelled each other out. In the wide target presentations, their effects were compounded and led to significant correlations between compression rate and localization error.